A 'Whole Systems' View of Vulnerability to Climatic Risks: The Case of the Urban Poor in Dhaka, Bangladesh. (April 2020) - Haque, Anika Nasra
The article aims to identify how varied factors (e.g., physical and socioeconomical) behind vulnerability of the urban poor in Dhaka's low-income settlements interact with each other to constitute their overall vulnerability. It addresses the complexity of the issues involved which cannot be understood by having partial look at their vulnerability. Hence, it suggests a 'whole systems' view to understand the underlying phenomenon. Data collected through mixed methods were analysed using a grounded theory-systems analysis approach. It identifies the reinforcing loops developed within the systems that strongly promote poverty traps and also identifies ways in which these vicious circles can be broken.